Movement Training Course View Scale Validity And Reliability of Study - Selahattin Akpınar; Merve Hasırcı; Pelin Ustaoğlu Hoşver (Türk Spor ve Egzersiz Dergisi)
Movement education is important for the development of children, so it should be ensured that children gain multiple experiences with movement education curriculum prepared by experts suitable for children's developmental periods. This should only be provided by experts who have taken or have taken the movement education course at universities' faculties of sports sciences or physical education and sports colleges. The aim of this research is to develop a valid and reliable scale in order to determine the attitudes of the students who take the movement education course towards the movement education course. The study group of this research consisted of 300 students, 178 of whom were enrolled in physical education and sports teaching and 122 of them were enrolled in the department of coaching education and took the movement training course, studying at the faculties of sports sciences and sports sciences schools of various universities in the spring semester of the 2021-2022 academic year. forms. 103 of the students are female and 197 are male. Cronbach Alpha coefficient was calculated to determine the reliability of the scale. As a result of expert opinion and exploratory factor analysis, a five-point Likert-type scale consisting of 26 items was obtained. The scale consists of three dimensions. In order to determine the internal consistency of the scale, the item-total correlation was calculated and it was seen that the correlation values of all items were high. The Cronbach Alpha reliability coefficient, which was calculated to determine the reliability of the scale, was calculated as .962. When the findings related to the validity and reliability studies of the scale are examined, it can be said that the scale is a valid and reliable measurement tool that can measure the attitudes of the students towards the movement education lesson.